Critical thinking skills of chemistry education students in team project-based STEM-metacognitive skills learning during the Covid19 pandemic - Ijirana Ijirana; Sitti Aminah; Supriadi Supriadi; Magfirah Magfirah (OmniaScience, 2022)
Critical thinking skills has to be sharpened particularly during the COVID19 pandemic. This circumstance leads to the lack of students passion to apply their thinking skills in doing something necessary. Therefore, it requires a learning improving critical thinking skills. This study aims to describe the critical thinking skills of chemistry education students taking part in the lecture of Team Project Based STEM-metacognitive skills. The method utilized is a Pre-Experimental Design One-Shot Case Study consists of 130 chemistry education students taking part in 3rd and 5th semester. The 3rd semester students attend lectures on the development of chemistry learning programs (P3K) and the 5th semester students attend lectures on the basics of analytical chemistry (DDKA). The instruments utilized in this research are learning scenarios, worksheets, critical thinking test instruments, critical thinking skill assessment rubrics, and project implementation feasibility observation sheets. There are three critical thinking skills very well demonstrated by students in P3K and DDKA subjects, consist of (1) strategies and tactics, (2) providing simple explanations, and (3) providing further explanations. Two other skills, namely concluding and building basic skills shown by students in the good category. The results of this study contribute to chemistry learning in the future, thus efforts are inevitably required to train critical thinking skills for prospective chemistry teachers in order to produce teachers having good thinking skills.